Effect of re-casting on release of elements from one base metal alloy - Farshad Bajoghli; Ehsan Ghasemi; Amir Yazdani (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Toxicity of dental alloys depends on their composition and element release, which may, in turn, be affected by re-casting of the alloy. The aim of this study was to evaluate the effect of re-casting on the release of elements from Verabond base metal alloy.Materials and Methods: In this laboratory study Verabond base metal alloy was evaluated. At first cubic wax patterns measuring 11×13×1.4 mm were prepared. Then alloy disks were cast as follows: 100% new alloy; 50% new with 50% re-cast alloy; and 100% re-cast alloy. Each alloy specimen was finished and polished under simulated clinical conditions and sterilized in an autoclave. Each specimen was conditioned in artificial saliva at 37°C for 72 hours. The specimens were retrieved from artificial saliva and release of elements from the alloys was investigated by Atomic Absorption Spectrophotometry. Data was analyzed by one-way ANOVA and a post hoc Tukey test (α = 0.05).Results: ANOVA revealed significant differences between the cast and re-cast Verabond groups; release of titanium, nickel, aluminum and chloride were respectively higher in recast alloys compared to cast alloys (p value < 0.05). The amounts of Be, Mo, Co were not quantified by spectrophotometry due to their low concentrations.Conclusion: Based on the results of the present study, re-casting of alloys significantly increases the release of elements. Therefore, re-casting of alloys should be avoided. Key words: Artificial saliva, Atomic Emission spectrophotometry, Dental casting alloy.